Crossing of Plasma Structures by Spacecraft: A Path Calculator. Issue 12 (11th December 2019) - Manuzzo, R.; Belmont, G.; Rezeau, L.; Califano, F.; Denton, R. E.
Abstract: When spacecraft (s/c) missions probe plasma structures (PSs) the relative location of the s/c with respect to the PS is unknown. This information is, however, needed to measure the geometrical features of the PS (orientation and thickness) and to understand the physical processes underlying the PS dynamics. Methods to determine the s/c location exist, but they need strong assumptions to be satisfied (stationarity and special spatial dependencies). The number of cases for which these assumptions are likely to be valid for the entire PS seems to be limited, and even weak departures from these hypotheses may affect the results. For a quasi‐1‐D geometry in particular, the determination of the velocity component along the two quasi‐invariant directions is very inaccurate and the assumption of strict stationarity may lead these quantities to diverge. In this paper we present new methods to compute the s/c trajectory through a PS, without a priori assumption on its spatial geometry, and able to work even in the presence of weak nonstationarities. The methods are tested both on artificial and real data, the latter provided by the Magnetospheric Multiscale mission probing the Earth's magnetopause. The 1‐D and 2‐D trajectories of the Magnetospheric Multiscale are found that can be used as an initial step for future reconstruction studies. Advanced minimization procedures to optimize the results are discussed. Key Points: The spatiotemporal difference method is extended to determine nonmonodimensional spacecraft trajectories Two new methods are developed for this determination: the single and the multivariate fit methods; they are compared to previous ones A gradient‐directed Monte Carlo approach is applied to optimize the results; the spacecraft path and magnetopause thickness are so computed